Indonesia–Japan Strategic Synergy in the Indo-Pacific: Contributions to Regional Stability - Handayani, Riska Sri; Yuliatiningtyas, Solikhah (Manunggal Halim Jaya, 2025)
This study examines how Indonesia and Japan, as influential middle powers, contribute to stability in the Indo-Pacific through complementary strategic frameworks. It asks: How can Indonesia's ASEAN Outlook on the Indo-Pacific (AOIP) and Japan's Free and Open Indo-Pacific (FOIP) be coordinated to strengthen regional security and peacebuilding? Using qualitative secondary data analysis, including policy documents, case studies, and media, the research applies Middle Power Theory and Strategic Narrative Theory to evaluate their diplomatic behavior and public messaging. The findings show that Indonesia's inclusive, consensus-based diplomacy aligns with Japan's economic and technological statecraft. Their partnership is most effective when policy coordination is reinforced by harmonized public diplomacy. Key areas for deeper collaboration include maritime security, sustainable development, and non-traditional security threats such as climate change and disaster response. By formalizing AOIP–FOIP coordination and expanding non-traditional security cooperation, Indonesia and Japan can enhance collective security and promote a rules-based regional order.